Menjadikan Pemilik Tanah Sebagai Pemegang Saham Perusahaan, Sebagai Alternatif Pembebasan Tanah Masyarakat - Amdanata, Donal Devi; Mansor, Noorhayati (Melayunesia Law, 2018)
This study aims to produce a model of the transfer of control of land without any permanent transfer of land rights. Basic theory used is the stakeholder theory and combined with agency theory. At this time, the company issues in land acquisition is a problem that was never completed. Companies require mastery of the land to increase production and increase investment. Problems arise if the property is controlled by a corporation that wants to belong to the community. The Company typically acquires land by following standard procedures. Starting from the issue of legality to the pricing of land acquisition, while the community determines the price of land acquisition by using market prices. The problem is further complicated when people use the market price, but not based on the calculation of appraisal, but based on rumors or general discussions in the community. So that the area acquisition price is higher than taxable value. The model determined by making the owner of the land as one of the shareholders in the capital structure of the company, or the firm appoints affiliated companies. With this model, the public ownership of the land or the landowner has not changed, and the company can use the desired area without a lot of money and time spent for land acquisition.